PROFIL PENYELESAIAN SOAL CERITA POLA BILANGAN PADA SISWA MTs ALKHAIRAAT TOMINI DITINJAU DARI EFIKASI DIRI - Safirah Safirah; Ibnu Hadjar; Welli Meinarni (Jurnal Elektronik Pendidikan Matematika Tadulako, 2025)
This study aims to obtain a description of the results of solving number pattern story problems in grade VIII MTs Alkhairaat Tomini students from the perspective of self-efficacy. This type of research is descriptive research with a qualitative approach. There are two subjects in this study, namely, subjects who have high self-efficacy and subjects who have low self-efficacy. The results of this study show that (1) related to understanding problems, subjects with high self-efficacy can mention and understand problems well, while subjects with low self-efficacy can mention information even though not as a whole. (2) in planning the problem solving, both subjects can determine the problem solving plan well, (3) in implementing the problem solving plan, the two subjects are consistent with the plan that has been made previously although, there is a mistake when the subject with low self-efficacy enters the value into the formula so that the results obtained are not correct. (4) related to re-examining the answers, subjects who have high self-efficacy re-examine the steps of the question processing process, while subjects who have low self-efficacy do not re-examine the steps to solve the question